Comparison of Llevel of improvement in serum albumin after protein supplementation verses standard treatment in patients on maintenance hemodialysis.: Intradialytic protein supplementation - Mirza, Shahrukh; Saleem, Nida; Mahmud, Syed Nayer; Haneef, Muhammad (Pakistan Journal of Kidney Diseases, 2022)
Background: Hemodialysis has been shown to increase protein catabolism and led to significant loss of proteins during hemodialysis. Hypoalbuminemia has been associated with adverse outcomes. Therefore, the main aim of this study is to determine the effect of intradialytic protein supplementation on serum albumin in hemodialysis patients. Methods: 116 hypoalbuminemic patients, as defined by the operational definition, on twice per week hemodialysis, from 15.09.15 to 15.03.16, were enrolled after obtaining informed consent. A non-randomized control trial was conducted after dividing the study population was divided into 2 groups; the study group which received 20g oral protein supplementation and the control group which have not received any supplementation. Outcome in terms of improvement in serum albumin was recorded on a predesigned proforma. SPSS version 17 was used for analysis. Effect modifiers were controlled by stratification. Chi square test was used to compare improvement in serum albumin between two groups and also after post stratification. Results: There were total 49 male and 67 female patients. Mean age of total patients was 57.25 years. 94.1% of the patients showed improvement in serum albumin in the intervention group and 56.9% in the control group. Patients of both genders between 46 to 75years, and those dialyzed for a shorter duration showed significant improvement in serum albumin levels. Conclusion: As intradialytic oral protein supplementation significantly improved serum albumin levels, specifically in elderly patients, it is therefore recommended to routinely administer nutritional supplements in hypoalbuminemic hemodialysis patients in order to reduce the overall mortality associated with hypoalbuminemia.